Automation and reallocation: The lasting legacy of COVID-19 in Canada - Joel Blit (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2020)
Recent evidence suggests that recessions play a crucial role in promoting automation and the reallocation of productive resources. Consistent with this, I show that in the three previous Canadian recessions, routine jobs were disproportionately lost. COVID-19 is likely to have a similar impact, but bigger because superimposed onto the usual recessionary transformational forces are health-specific incentives to automate. Using O*NET data, I construct an index of COVID-19 health risk and of routine task intensity to measure health incentives to automate and the feasibility of doing so. Across occupations, income groups, industries, and regions, the two indices are strongly negatively correlated, suggesting that automation will not be overly focused and that it may penetrate into hitherto relatively unaffected sectors like health and education. Nevertheless, office and health support workers are likely to be disproportionately affected, as will the retail and hospitality industries. The impacts will also be primarily felt by families toward the bottom of the income distribution and in smaller cities.
Keywords: O33; O40; E32; J24; 330; COVID-19; recessions; productivity; innovation; automation